2014
DOI: 10.1002/phy2.193
|View full text |Cite
|
Sign up to set email alerts
|

Acute impact of retrograde shear rate on brachial and superficial femoral artery flow-mediated dilation in humans

Abstract: Retrograde shear rate (SR) in the brachial artery (BA) is associated with endothelial dysfunction; a precursor to atherosclerosis. The BA does not typically manifest clinical atherosclerosis, whereas the superficial femoral artery (SFA) is more prone to developing plaque. Examine whether the impact of incremental levels of retrograde SR differs between atherosclerosis‐prone (i.e., SFA) and ‐resistant vessels (i.e., BA) in healthy men. Thirteen healthy young men reported three times to the laboratory. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
80
2
9

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 33 publications
14
80
2
9
Order By: Relevance
“…In this manner, this study successfully introduced compression sleeves as a method to manipulate retrograde SR, both acutely and chronically in men in vivo. Although a nonsignificant increase was found in antegrade SR in both young and older men, the main observation was that we (in line with our previous work) successfully manipulated retrograde shear 2, 12, 39. Although we only explored the impact of the sleeve intervention on resting levels of retrograde shear, we are confident that increased levels of retrograde SR were also present during various activities of daily living.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In this manner, this study successfully introduced compression sleeves as a method to manipulate retrograde SR, both acutely and chronically in men in vivo. Although a nonsignificant increase was found in antegrade SR in both young and older men, the main observation was that we (in line with our previous work) successfully manipulated retrograde shear 2, 12, 39. Although we only explored the impact of the sleeve intervention on resting levels of retrograde shear, we are confident that increased levels of retrograde SR were also present during various activities of daily living.…”
Section: Discussionsupporting
confidence: 76%
“…In previous studies, we used pneumatic cuffs to manipulate retrograde shear acutely 2, 12. For chronic shear manipulation, however, blood pressure cuffs are impractical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conduit artery shear rate patterns are affected by downstream vascular resistance 2,11,12) . Previous research has demonstrated that acute elevations in vascular resistance that occur via an increase in muscle sympathetic nerve activity (MSNA) with lower body negative pressure (LBNP) are associated with an increase in conduit artery retrograde and oscillatory shear 12) Moreover, Casey et al reported that α-adrenergic vasoconstriction of the downstream resistance vessels is a major contributor to agerelated increases in conduit arteries retrograde and oscillatory shear at rest 8) .…”
Section: Introductionmentioning
confidence: 99%
“…Shear stress demonstrates a typical pattern (i.e., antegrade and retrograde shear) in conduit arteries. Elevation in retrograde and oscillatory shear may have pro-atherogenic effects [1][2][3][4][5][6] . Aging causes increased retrograde shear and oscillatory shear in peripheral conduit arteries [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%